Intrathecal [6]‐Gingerol Administration Alleviates Peripherally induced Neuropathic Pain in Male Sprague–Dawley Rats. (12th September 2012) - Gauthier, Marie‐Lou; Beaudry, Francis; Vachon, Pascal
<x xml:space="preserve">Abstract</x> [6]‐Gingerol, a structural analog of capsaicin, is an agonist of the transient receptor potential vanilloid 1 channel, which is known to have therapeutic properties for the treatment of pain and inflammation. The main objective of this study was to determine the central effect of [6]‐gingerol on neuropathic pain when injected intrathecally at the level of the lumbar spinal cord. [6]‐Gingerol distribution was evaluated following a 40 mg/kg intraperitoneal injection, and the brain‐to‐plasma and spinal cord‐to‐plasma ratios (0.73 and 1.7, respectively) suggest that [6]‐gingerol penetrates well the central nervous system of rats. Induction of pain was performed using the sciatic nerve ligation model on rats, and a 10‐µg intrathecal injections of [6]‐gingerol was performed to evaluate its central effect. The results suggest a significant decrease of secondary mechanical allodynia after 30 min, 2 h and 4 h (p < 0.05, p < 0.01 and p < 0.001) and thermal hyperalgesia after 30 min, 2 h and 4 h (p < 0.05, p < 0.01 and p < 0.01). These promising results illustrate that [6]‐gingerol could alleviate neuropathic pain by acting centrally at the level of the spinal cord. Copyright © 2012 John Wiley & Sons, Ltd.